Examining Institutional Ownership and Audit Committee Characteristics: CSR's Role in Tax Avoidance Practices - Rudiatun, Rika; Anggorowati, Ayu (Indonesian Journal of Sustainability Policy and Technology, 2024)
This study examines the influence of institutional ownership, audit committee size, and the financial and accounting expertise of audit committee members on tax avoidance practices, with corporate social responsibility (CSR) serving as a mediating variable. This research utilizes a quantitative methodology, concentrating on manufacturing firms within the food and beverage sub-sector listed on the Indonesia Stock Exchange during the period from 2017 to 2021. Purposive sampling was employed to select 23 companies as the final sample. The analysis utilized the Structural Equation Model (SEM) through SmartPLS software. The findings indicate that institutional ownership, the size of the audit committee, and the financial expertise of audit committee members do not significantly impact tax avoidance. Institutional ownership positively affects CSR, while the size of the audit committee negatively influences CSR. The financial and accounting expertise of audit committee members does not significantly impact corporate social responsibility (CSR). Furthermore, CSR does not mediate the relationships among institutional ownership, audit committee size, and financial expertise concerning tax avoidance. The research indicates that organizations ought to reduce tax avoidance to more effectively meet their fiscal obligations. Policymakers should implement stricter tax regulations to mitigate tax avoidance practices.